PROFESSOR VLADIMIR ANDREEVICH POLYANSKIY – NEUROSURGEON, ABDOMINAL SURGEON, TRANSFUSIOLOGIST (to the 80th anniversary of his birth) - A. N. Lischenko; N. V. Bosak (Кубанский научный медицинский вестник, 2018)
The development of neurosurgery in the Kuban region is connected with the work of Professor V.A. Polyansky, who implemented in practical health care vertebral angiography for tumors of posterior cranial fossa, first in the Northern Caucasus, deleted cysticercus of IV ventricle of the brain. Principles of peritonitis treatment and infusion therapy described by V.A. Polyansky in the 70s of the 20th century, have not lost their relevance to the present day. In addition to surgical interventions and development of optimal methods of abdominal drainage, peritoneal dialysis, infusion therapy and parenteral nutrition were used; methods of dealing with paralysis of the gastrointestinal tract and an increase in intraabdominal pressure were examined.